Akomodasi Hukum Yang Hidup Dalam Kuhp Baru Indonesia Menurut Perspektif Hukum Progresif - Magala, Anugrah Sahtia (Jurnal Spektrum Hukum PMIH UNTAG Semarang, 2023)
Legal accommodation living in the national criminal law system is an important orientation in criminal law reform after the enactment of Law No. 1 of 2023 concerning the Criminal Code. This change is aimed at integrating living law as an instrument in achieving substantive justice in Indonesia. This research was conducted using juridical-normative methods and statutory approaches, specifically by elaborating Article 2 of Law No. 1 of 2023 concerning the Criminal Code and examining living legal accommodation arrangements using a progressive legal perspective. Progressive law was chosen as the perspective in this study because of its relevance to the movement of criminal code reform in Indonesia. The results of this study are divided into shows that the legal formulation that lives in the Criminal Code is in accordance with progressive legal concepts and values, including deconstructing legal positivism by expanding the principle of legality, applying a holistic paradigm, and reorienting legal goals to substantive justice. However, there is an important note related to the potentiality of legal arrangements living in local regulations that can tend to positivization, which has an impact on the phenomenon of norm reductionism. Hukum yang hidup dan telah terpositivisasi dapat kehilangan esensinya dan menjadi hukum positif. The progressive legal perspective directs that derivative arrangements of the Criminal Code be carefully formulated by aligning themselves with the five missions of the Criminal Code. The purpose of this study is to provide a comprehensive picture of progressive legal perspectives in legal accommodation that lives in the Criminal Code, so that it can be a guideline for policymakers in formulating strategies for implementing the Criminal Code in public life in Indonesia.